The Effect of Light Intensity and Polyethylene-Glycol-Induced Water Stress on the Growth, Mitragynine Accumulation, and Total Alkaloid Content of Kratom (Mitragyna speciosa) - Nisa Leksungnoen; Tushar Andriyas; Yongkriat Ku-Or; Suthaporn Chongdi; Rossarin Tansawat; Attawan Aramrak; Chatchai Ngernsaengsaruay; Suwimon Uthairatsamee; Weerasin Sonjaroon; Phatthareeya Thongchot; Sirinapa Ardsiri; Pichaya Pongchaidacha (Horticulturae)
The cultivation of Mitragyna speciosa (kratom) has gained significant interest due to its diverse alkaloid profile, increasing its commercial and medicinal demand. Using controlled hydroponic techniques, this study investigates the effects of varying light intensity and water potential on kratom growth, mitragynine (MG) accumulation, and total alkaloid content (TAC). While the interaction between light and water potential was generally not significant, water potential emerged as the dominant factor affecting plant growth and alkaloid accumulation. The highest MG accumulation (0.63% w/w) was recorded under moderate water potential (−0.4 MPa). In contrast, the highest TAC (8.37 mg alkaloid equivalent per gram dry weight) was observed under the combined effect of low light and mild water potential (−0.4 MPa). Leaf age also played a key role, with younger leaves (second and third pairs) accumulating significantly higher MG levels (0.74% w/w) than older leaves (0.40% w/w). Additionally, leaf thickness was positively associated with MG levels, suggesting a potential link between plant morphology and alkaloid biosynthesis. However, low water potential (−0.7 MPa) significantly reduced both growth and MG content, highlighting the importance of optimizing environmental conditions for sustained bioactive compound production. These findings demonstrate the physiological adaptability of kratom to variable environmental stresses and their influence on alkaloid accumulation. This knowledge can be applied to precision cultivation strategies to enhance the sustainability of kratom farming while optimizing the production of bioactive compounds for pharmaceutical and agricultural applications.